Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To prove the given trigonometric identity \(\frac{2 \sec \theta + 1}{\cos \theta + 2} = \frac{\sqrt{a^2 + b^2}}{b}\), we start with the known relation \(\cot \theta = \frac{b}{a}\).
1. Express \(\cot \theta\) in terms of \(\cos \theta\) and \(\sin \theta\):
[tex]\[ \cot \theta = \frac{\cos \theta}{\sin \theta} \][/tex]
Given \(\cot \theta = \frac{b}{a}\), we have:
[tex]\[ \frac{\cos \theta}{\sin \theta} = \frac{b}{a} \][/tex]
2. Relate \(\cos \theta\) and \(\sin \theta\) using the Pythagorean identity:
[tex]\[ \cos^2 \theta + \sin^2 \theta = 1 \][/tex]
Since \(\cot \theta = \frac{\cos \theta}{\sin \theta}\), we can write:
[tex]\[ \cos \theta = \frac{b}{a} \sin \theta \][/tex]
3. Solve for \(\sin \theta\) and \(\cos \theta\):
Substitute \(\cos \theta = \frac{b}{a} \sin \theta\) into the Pythagorean identity:
[tex]\[ \left( \frac{b}{a} \sin \theta \right)^2 + \sin^2 \theta = 1 \][/tex]
[tex]\[ \frac{b^2}{a^2} \sin^2 \theta + \sin^2 \theta = 1 \][/tex]
[tex]\[ \left( \frac{b^2 + a^2}{a^2} \right) \sin^2 \theta = 1 \][/tex]
[tex]\[ \sin^2 \theta = \frac{a^2}{a^2 + b^2} \][/tex]
[tex]\[ \sin \theta = \frac{a}{\sqrt{a^2 + b^2}} \][/tex]
Therefore:
[tex]\[ \cos \theta = \frac{b}{a} \cdot \frac{a}{\sqrt{a^2 + b^2}} = \frac{b}{\sqrt{a^2 + b^2}} \][/tex]
4. Express \(\sec \theta\):
\(\sec \theta\) is the reciprocal of \(\cos \theta\):
[tex]\[ \sec \theta = \frac{1}{\cos \theta} = \frac{\sqrt{a^2 + b^2}}{b} \][/tex]
5. Substitute \(\sec \theta\) and \(\cos \theta\) into the left-hand side:
We need to prove:
[tex]\[ \frac{2 \sec \theta + 1}{\cos \theta + 2} = \frac{\sqrt{a^2 + b^2}}{b} \][/tex]
Substitute:
[tex]\[ \frac{2 \cdot \frac{\sqrt{a^2 + b^2}}{b} + 1}{\frac{b}{\sqrt{a^2 + b^2}} + 2} \][/tex]
6. Simplify the left-hand side:
Simplify the numerator:
[tex]\[ 2 \cdot \frac{\sqrt{a^2 + b^2}}{b} + 1 = \frac{2\sqrt{a^2 + b^2}}{b} + 1 = \frac{2\sqrt{a^2 + b^2} + b}{b} \][/tex]
Simplify the denominator:
[tex]\[ \frac{b}{\sqrt{a^2 + b^2}} + 2 = \frac{b + 2\sqrt{a^2 + b^2}}{\sqrt{a^2 + b^2}} \][/tex]
Now combine:
[tex]\[ \frac{2\sqrt{a^2 + b^2} + b}{b} \cdot \frac{\sqrt{a^2 + b^2}}{b + 2\sqrt{a^2 + b^2}} = \frac{(2\sqrt{a^2 + b^2} + b)\sqrt{a^2 + b^2}}{b(b + 2\sqrt{a^2 + b^2})} \][/tex]
7. Rewriting and final simplification:
After combining, the left-hand side simplifies due to the trigonometric identities:
[tex]\[ \frac{(2 \sqrt{a^2 + b^2} + b) \cdot \sqrt{a^2 + b^2}}{b \cdot (b + 2 \sqrt{a^2 + b^2})} = \frac{\sqrt{a^2 + b^2}}{b} \][/tex]
Thus, we have shown that:
[tex]\[ \frac{2 \sec \theta + 1}{\cos \theta + 2} = \frac{\sqrt{a^2 + b^2}}{b} \][/tex]
which completes the proof.
1. Express \(\cot \theta\) in terms of \(\cos \theta\) and \(\sin \theta\):
[tex]\[ \cot \theta = \frac{\cos \theta}{\sin \theta} \][/tex]
Given \(\cot \theta = \frac{b}{a}\), we have:
[tex]\[ \frac{\cos \theta}{\sin \theta} = \frac{b}{a} \][/tex]
2. Relate \(\cos \theta\) and \(\sin \theta\) using the Pythagorean identity:
[tex]\[ \cos^2 \theta + \sin^2 \theta = 1 \][/tex]
Since \(\cot \theta = \frac{\cos \theta}{\sin \theta}\), we can write:
[tex]\[ \cos \theta = \frac{b}{a} \sin \theta \][/tex]
3. Solve for \(\sin \theta\) and \(\cos \theta\):
Substitute \(\cos \theta = \frac{b}{a} \sin \theta\) into the Pythagorean identity:
[tex]\[ \left( \frac{b}{a} \sin \theta \right)^2 + \sin^2 \theta = 1 \][/tex]
[tex]\[ \frac{b^2}{a^2} \sin^2 \theta + \sin^2 \theta = 1 \][/tex]
[tex]\[ \left( \frac{b^2 + a^2}{a^2} \right) \sin^2 \theta = 1 \][/tex]
[tex]\[ \sin^2 \theta = \frac{a^2}{a^2 + b^2} \][/tex]
[tex]\[ \sin \theta = \frac{a}{\sqrt{a^2 + b^2}} \][/tex]
Therefore:
[tex]\[ \cos \theta = \frac{b}{a} \cdot \frac{a}{\sqrt{a^2 + b^2}} = \frac{b}{\sqrt{a^2 + b^2}} \][/tex]
4. Express \(\sec \theta\):
\(\sec \theta\) is the reciprocal of \(\cos \theta\):
[tex]\[ \sec \theta = \frac{1}{\cos \theta} = \frac{\sqrt{a^2 + b^2}}{b} \][/tex]
5. Substitute \(\sec \theta\) and \(\cos \theta\) into the left-hand side:
We need to prove:
[tex]\[ \frac{2 \sec \theta + 1}{\cos \theta + 2} = \frac{\sqrt{a^2 + b^2}}{b} \][/tex]
Substitute:
[tex]\[ \frac{2 \cdot \frac{\sqrt{a^2 + b^2}}{b} + 1}{\frac{b}{\sqrt{a^2 + b^2}} + 2} \][/tex]
6. Simplify the left-hand side:
Simplify the numerator:
[tex]\[ 2 \cdot \frac{\sqrt{a^2 + b^2}}{b} + 1 = \frac{2\sqrt{a^2 + b^2}}{b} + 1 = \frac{2\sqrt{a^2 + b^2} + b}{b} \][/tex]
Simplify the denominator:
[tex]\[ \frac{b}{\sqrt{a^2 + b^2}} + 2 = \frac{b + 2\sqrt{a^2 + b^2}}{\sqrt{a^2 + b^2}} \][/tex]
Now combine:
[tex]\[ \frac{2\sqrt{a^2 + b^2} + b}{b} \cdot \frac{\sqrt{a^2 + b^2}}{b + 2\sqrt{a^2 + b^2}} = \frac{(2\sqrt{a^2 + b^2} + b)\sqrt{a^2 + b^2}}{b(b + 2\sqrt{a^2 + b^2})} \][/tex]
7. Rewriting and final simplification:
After combining, the left-hand side simplifies due to the trigonometric identities:
[tex]\[ \frac{(2 \sqrt{a^2 + b^2} + b) \cdot \sqrt{a^2 + b^2}}{b \cdot (b + 2 \sqrt{a^2 + b^2})} = \frac{\sqrt{a^2 + b^2}}{b} \][/tex]
Thus, we have shown that:
[tex]\[ \frac{2 \sec \theta + 1}{\cos \theta + 2} = \frac{\sqrt{a^2 + b^2}}{b} \][/tex]
which completes the proof.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.